2017
DOI: 10.1039/c7ob00122c
|View full text |Cite
|
Sign up to set email alerts
|

Copper-catalyzed aerobic oxidative coupling of o-phenylenediamines with 2-aryl/heteroarylethylamines: direct access to construct quinoxalines

Abstract: A copper-catalyzed oxidative coupling reaction of o-phenylenediamines with 2-aryl/heteroarylethylamines using molecular oxygen as an oxidant has been developed. This approach provides a practical and direct access to construct quinoxalines in excellent yields at room temperature. The reaction has a broad substrate scope and exhibits excellent functional-group tolerance. This method could be easily scaled up and applied to the synthesis of biologically active molecules bearing a quinoxaline structural scaffold.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 87 publications
0
14
0
1
Order By: Relevance
“…Synthesis of quinoxaline via double condensation of 1,2-phenylenediamines with phenylglyoxals in the presence of a catalyst is a well-established concept in organic synthesis. 14 a Hashmi et al reported gold and silver bi-metal co-catalyzed synthesis of quinoxaline derivatives from terminal alkynes which involved the oxidation of phenyl acetylene to phenylglyoxals using external oxidant pyridine N-oxide (4 equiv.) 14 b (Scheme S6, ESI † ).…”
Section: Resultsmentioning
confidence: 99%
“…Synthesis of quinoxaline via double condensation of 1,2-phenylenediamines with phenylglyoxals in the presence of a catalyst is a well-established concept in organic synthesis. 14 a Hashmi et al reported gold and silver bi-metal co-catalyzed synthesis of quinoxaline derivatives from terminal alkynes which involved the oxidation of phenyl acetylene to phenylglyoxals using external oxidant pyridine N-oxide (4 equiv.) 14 b (Scheme S6, ESI † ).…”
Section: Resultsmentioning
confidence: 99%
“…近年来,在材料科学领域中,新型有机/无机杂化材 料正引起人们的广泛关注。该类材料由于有机和无机组分 的协同效应,使其具有突出的性能,在光、电、磁等领域 具有广泛的应用前景 [1][2][3]。 有机共轭聚合物(COPs)是一类非常特殊的聚合物功 能材料,由于其独特的共轭结构,导电性,电化学活性, 使它们成为功能聚合物功能材料研究的热点 [4][5][6][7][8][9]。比如, 芳胺聚合物中的聚苯胺在常温下经过化学和电化学掺杂 过程使其具有优异的导电性能,并且由于其易于合成、原 料易得、结构多样化、掺杂原理独特、导电性和稳定性好 等优势,是目前最具应用前景的导电聚合物。而聚苯二胺 作为一种重要的芳香二胺类聚合物,因为其大分子结构中 含有比聚苯胺较多的活性自由氨基和亚胺基,并且还拥有 多功能性,近年来已被广泛关注 [10][11][12][13][14][15]。 普鲁士蓝(prussian blue, PB)及其衍生物是一种混合价 态的化合物。 其具有优良的电化学可逆性, 高度的稳定性, 容易制备等优点, 因此在化学修饰电极、 电显示、 电催化、 二次储能电池等方面有很大的应用前景 [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]…”
Section: .引言unclassified
“…18 Nevertheless, at a slightly more elevated temperature of 130 °C for 24 hours, CuI was also able to catalyze the oxidation of 2-phenylethylamine, which, in the presence of o-phenylenediamine, was converted into a sixmembered 2-phenylquinoxaline product through a reaction mechanism recently reported by Gopalaiah and coworkers for their similar CuBr-catalyzed protocol (Scheme 7, dashed arrows). 20 In the presence of o-phenylenediamine (A), copper-catalyzed aerobic oxidation of 2-phenylethylamine produces the cross-coupled imine B which, after copper-catalyzed benzylic oxidation, leads to the formation of the keto-imine E via benzyl radical intermediate C and hydroperoxide D.…”
Section: Metal-catalyzed Reactionsmentioning
confidence: 99%